Use of ethrel on the mechanized and selective coffee (Coffea arabica L.) harvest - Silva, Fábio Moreira da; Arré, Tadeu Jorge; Tourino, Ely de Souza; Gomes, Túlio Seabra; Alves, Marcelo de Carvalho (Coffee Science - ISSN 1984-3909, 1970)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.MsoTitle, li.MsoTitle, div.MsoTitle {mso-style-unhide:no; mso-style-qformat:yes; mso-style-link:"Título Char"; margin:0cm; margin-bottom:.0001pt; text-align:center; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; font-weight:bold;} span.TtuloChar {mso-style-name:"Título Char"; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:Título; mso-ansi-font-size:12.0pt; mso-bidi-font-size:12.0pt; font-weight:bold;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Ethrel is a physiological maturation accelerator, which has been applied to coffee crops through wet solution for fruit maturation standardization, acting as an accelerator, anticipating and increasing the efficiency of the coffee harvest. This work was conducted at Palmito farm, located in Boa Esperança city, south of Minas Gerais, on the Mundo Novo cultivar. The application of Ethrel was conducted in 30 plants per plot, with three repetitions, with a dosage of 0.67 L / ha at a rate of 505 litres per hectare. The harvest was done with two runs of the harvester along the field, at 29 and 61 days after the application of Ethrel. After two harvester runs, the volume of harvested cherries was 3.5 and 5.4 L / plant, for the treatments with and without Ethrel, respectively. The quality of the drink, based on the cupping test, was not influenced by treatments with or without Ethrel, considering the two runs of the harvester along the field.